Testing for drug-human serum albumin binding using fluorescent probes and other methods. (2nd November 2018) - Ronzetti, Michael; Baljinnyam, Bolormaa; Yasgar, Adam; Simeonov, Anton
ABSTRACT: Introduction : Drug plasma protein binding remains highly relevant to research and drug development, making the assessment and profiling of compound affinity to plasma proteins essential to drug discovery efforts. Although there are a number of fully-characterized methods, they lack the throughput to handle large numbers of compounds. As the evaluation of adsorption, distribution, metabolism, and excretion is addressed earlier in the drug development timeline, the need for higher-throughput methods has grown. Areas Covered : This review will highlight recent developments on methods for profiling drug plasma binding, with an emphasis on fluorescent probes and emerging high-throughput methodologies. Expert Opinion : There have been a number of high-throughput assays developed in recent years to meet the scaled up demands for compound profiling. Ultimately, the selection of assay technology relies on a number of factors, such as capabilities of the laboratory and the breadth and amount of data required. Fluorescent probe displacement assays are highly flexible and amenable to high-throughput screening, easily scaling up to handle large compound libraries. Recent developments in fluorescence technologies, such as homogenous time-resolved fluorescence and probes utilizing the aggregation-induced emission effect, have improved the sensitivity of these assays. Other technologies, such as microscale thermophoresis and quantitative structure-activity relationship modeling, are gaining popularity as alternative techniques for drug plasma protein binding characterization.